Dynamics of Factor Income Shares in the United States - Jefferson, Philip N.; Pryor, Frederic L. (Journal of Income Distribution®, 2010)
This essay examines the cyclical behavior and stability properties of four different measures of the labor share of income in the United States from 1948 through 2006. The evidence suggests that the share exhibits instability. This instability is sensitive to the measure of labor share deployed and whether that measure has been adjusted for the changing sectoral composition of production over time. We test a number of competing hypotheses about the determinants of the behavior of cyclical labor share, showing that its movements are traceable to just two indicators of the business cycle, namely lagged gross domestic product (GDP) and lagged multifactor productivity.